The Role of Interpersonal Communication Between Parents and Children in Building Children's Learning Motivation at Penghuluan Ujung Tanjung, Tanah Putih District (International Journal of Cultural and Social Science, 2023)
Communication is an important thing in life, even every living individual cannot escape from the social environment. Parents are the most important part in exchanging information especially in learning. Parents as the first madrasah as a place to educate and guide children must pay attention to the growth and development of children as a nation's regeneration. The purpose of this study is to find out how the role of interpersonal communication between parents and children in building learning motivation and what are the inhibiting factors.